2003
DOI: 10.1302/0301-620x.85b7.13672
|View full text |Cite
|
Sign up to set email alerts
|

Histological evaluation of chondral defects after autologous chondrocyte implantation of the knee

Abstract: We have performed a prospective, single-surgeon study analysing the histological results of autologous chondrocyte implantation. Fourteen patients underwent autologous chondrocyte implantation of the knee and were evaluated at one year by clinical assessment and arthroscopy. Standard staining was used to examine the sections. In addition, in situ hybridisation was used to establish type-IIa and type-IIb collagen mRNA expression and immunolocalisation techniques demonstrated the positions of type-II and type-X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(92 citation statements)
references
References 23 publications
(46 reference statements)
5
78
1
6
Order By: Relevance
“…It appears that all interventions are mostly successful in the short-term. Second, results in the trials differ, with Knutsen and colleagues 63 finding fibrocartilage in biopsies after ACI, whereas Briggs and colleagues 66 found hyaline in about half. Third, the distinction between hyaline cartilage and fibrocartilage may be too crude; more sophisticated ways of assessing the quality of regenerating cartilage may provide better predictors of later success.…”
Section: Conclusion From Economic Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…It appears that all interventions are mostly successful in the short-term. Second, results in the trials differ, with Knutsen and colleagues 63 finding fibrocartilage in biopsies after ACI, whereas Briggs and colleagues 66 found hyaline in about half. Third, the distinction between hyaline cartilage and fibrocartilage may be too crude; more sophisticated ways of assessing the quality of regenerating cartilage may provide better predictors of later success.…”
Section: Conclusion From Economic Analysismentioning
confidence: 99%
“…Briggs and colleagues 66 carried out biopsies in 14 patients 1 year after ACI. Eight patients had hyaline cartilage (six had hyaline only, two had mixed hyaline and fibrocartilage) and the others had fibrocartilage.…”
Section: Histologymentioning
confidence: 99%
See 1 more Smart Citation
“…Nach Anzucht einer ausreichenden Zellzahl werden sie unter einen wasserdicht aufgenähten Periostlappen injiziert [12]. Im weiteren Verlauf entsteht in den meisten Fällen ein Gewebe, das dem hyalinen Gelenkknorpel in seinen Eigenschaften sehr nahe kommt [11,37,41]. Auch nach langen Verlaufszeiten wurden von Peterson et al [38,39] …”
Section: Autologe Chondrozytentransplantation (Act)unclassified
“…The cell suspension is retained by either a patch of periosteum or a commercially available collagen membrane, sutured to the edges of the defect and sealed with fibrin. Our center has used ACI in approximately 500 procedures and we and others have shown that it has the potential to improve functional outcome [2][3][4] and generate repair tissue that offers a durable surface and is well integrated with the surrounding cartilage [5][6][7][8]. In our audits of ACI, 80% of patients improve by 15 months, and this improvement is sustained for 9-16 years [3,9].…”
mentioning
confidence: 98%